2022
DOI: 10.29133/yyutbd.1060036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality and Some Agronomic Traits of Bread Wheat (Triticum aestivum L.) Lines and Cultivars under Kahramanmaraş Ecological Conditions

Abstract: In this study, eight promising advanced bread wheat genotypes derived from breeding programs and Ceyhan-99, Sagittario, Masaccio, and Seri-82 commercial cultivars were used as materials. The experiments were carried out in 2018-2019 and 2019-2020 cropping years in a randomized complete block design with four replications. In the study, some agronomic and quality traits were investigated. Bread wheat genotypes varied significantly for all investigated traits in terms of the year, genotype, and year x genotype i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Test weight changes according to factors such as genotypic performance, environmental conditions, agricultural techniques, illnesses, and pests. Furthermore, biotic and abiotic factors that cause the wheat grain to remain tiny influence the test weight (Yuce et al, 2022). Furthermore, while environmental factors such as precipitation and temperature during the growing season influence test weight, structural characteristics of the grain such as grain filling, length of vegetation period, grain size and shape, abdominal cavity, and wrinkling also influence it (Aguirre et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Test weight changes according to factors such as genotypic performance, environmental conditions, agricultural techniques, illnesses, and pests. Furthermore, biotic and abiotic factors that cause the wheat grain to remain tiny influence the test weight (Yuce et al, 2022). Furthermore, while environmental factors such as precipitation and temperature during the growing season influence test weight, structural characteristics of the grain such as grain filling, length of vegetation period, grain size and shape, abdominal cavity, and wrinkling also influence it (Aguirre et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Since wheat is of great importance in human nutrition worldwide, one of the most important targets of wheat breeders is to increase the grain yield (GY) obtained per unit area (Aktas, 2016;Barutcular et al, 2017;Yildirim et al, 2018;Kizilgeci et al, 2019a). Optimizing agronomic applications and developing varieties with high yield capacity are two main factors in increasing GY (Aktas, 2016;Güngör and Dumlupınar, 2019;Yüce et al, 2022). Different statistical methods are used in the evaluation of genotypes according to the data obtained in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Agro-morphological characterization (Ghimire and Magar, 2017) and genotyping-by-sequencing (GBS) results in both showed that there is a high genetic diversity among Nepalese wheat landraces (Khadka et al, 2020). A crucial step in managing and utilizing the genetic diversity of any crop and for the development of better varieties is agro-morphological characterization (Manzano et al, 2001;Ali et al, 2022;Yüce et al, 2022). Smith and colleagues (1991) stated that significant traits of local landraces need to be assessed, characterized, and labeled.…”
Section: Introductionmentioning
confidence: 99%